Lumen diameter variation of hand radial artery in cadaver anatomical snuffbox - Leonardo Lubis; Gita Tiara Dewi Nasution; Adilla Zulfana Hermawan (Bali Anatomy Journal, 2021)
Background: The most recent finding in interventional cardiology is "more distal radial accesses." The success rate of this access reached 97,7%. Variation in lumen diameter at the puncture site can be a contributing factor to access failure. However, this variation has not been well recorded due to the absence of studies regarding it. Aim: To determine the variation of the lumen diameter of the distal radial artery in the anatomical snuffbox. Methods: This study was an observational study on 13 cadavers with a total of 25 hands. Dissection of the cadaver was done by the anatomical dissection method, and the lumen diameter was measured. Results: Descriptive measurement showed significant variation in lumen diameter of the distal radial artery. Conclusion: There is medium to very high variation in lumen diameter based on hand side, gender, and both.